2013
DOI: 10.1111/anu.12062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of potential probioticBacillus subtilisVSG1 singularly or in combination withLactobacillus plantarumVSG3 or/andPseudomonas aeruginosaVSG2 on the growth, immunity and disease resistance ofLabeo rohita

Abstract: Labeo rohita fingerlings were fed for 60 days with basal diet (BD) or one of the following experimental diets: DI (BD + B. subtilis); DII (BD + B. subtilis + L. plantarum); DIII (BD + B. subtilis + P. aeruginosa) and DIV (BD + B. subtilis + P. aeruginosa + L. plantarum). Various growth and immune parameters were examined at 30 and 60 days postfeeding. The fish group fed DIV diet had better improvement (P < 0.05) in weight gain, specific growth rate (SGR) and feed conversion ratio (FCR) than the control and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 34 publications
9
56
0
1
Order By: Relevance
“…These results were in agreement with a previously reported study by Zhao et al [17], in which sea cucumbers fed a diet supplemented with Bacillus subtilis T13. Enhanced phagocytosis and/or respiratory burst activities were also observed in the leukocytes of gilthead seabream (Sparus aurata) [48] and the head kidney macrophages of cobia (Rachycentron canadum) [49] and Labeo rohita [50] when fed diets supplemented with Bacillus spp. The phosphatase enzymes are capable of hydrolyzing organic phosphate esters.…”
Section: Discussionmentioning
confidence: 92%
“…These results were in agreement with a previously reported study by Zhao et al [17], in which sea cucumbers fed a diet supplemented with Bacillus subtilis T13. Enhanced phagocytosis and/or respiratory burst activities were also observed in the leukocytes of gilthead seabream (Sparus aurata) [48] and the head kidney macrophages of cobia (Rachycentron canadum) [49] and Labeo rohita [50] when fed diets supplemented with Bacillus spp. The phosphatase enzymes are capable of hydrolyzing organic phosphate esters.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, cellular components of the probiotics Kocuria SM1 and Rhodococcus SM2 increased IgM levels in Oncorhynchus mykiss (Sharifuzzaman et al, 2011). Earlier studies demonstrated that probiotic supplementation increased IgM levels in fish at an initial time point; however, at later time points, these levels declined (Sun et al, 2010; Giri et al, 2013, 2014). In this study, IgM levels increased initially and thereafter they decreased gradually, suggesting that IgM increases is a temporary phenomenon attributable to immunostimulants.…”
Section: Discussionmentioning
confidence: 94%
“…IgM is the predominant antibody type in fish. It is used to identify and neutralize foreign objects such as bacteria and viruses (Giri et al, 2014). Similarly, cellular components of the probiotics Kocuria SM1 and Rhodococcus SM2 increased IgM levels in Oncorhynchus mykiss (Sharifuzzaman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus and Cornobacterium), the genus Bacillus, photosynthetic bacteria (e.g. Rhodobacter sphaeroides), yeasts, Pseudomonas or Vibrio, though other genera and/or species have also been used [3,20,25,28,38]. Iron (Fe) is an essential element in the cellular respiratory process through its oxidation-reduction and electron transfer activities.…”
Section: Introductionmentioning
confidence: 99%